Optimization Ultrasound-Assisted Deep Eutectic Solvent Extraction of Anthocyanins from Raspberry Using Response Surface Methodology Coupled with Genetic Algorithm - Xue, Hongkun (Foods, 2020)
Raspberries have been reported to contain abundant anthocyanins and other active compounds. To extract anthocyanins from raspberries more efficiently, a novel procedure of ultrasound-assisted deep eutectic solvent extraction (UADESE) was proposed in this paper. The extraction process was optimized by response surface methodology coupled with a genetic algorithm. The optimum extraction parameters to achieve the highest yield of anthocyanins 1.378 ± 0.009 mg/g from raspberry powder via UADESE were obtained at a water content of 29%, ultrasonic power of 210 W, extraction temperature of 51 °C and extraction time of 32 min. The AB-8 macroporous resin combined with the high-speed counter current chromatography (HSCCC) method were further used to isolate and purify the anthocyanins extracts obtained under optimum extraction conditions, and the structure of purified anthocyanins components were identified by UV-Visible spectrophotometer (UV-Vis), high-performance liquid chromatography (HPLC), high-performance liquid chromatography-electrospray ionization-mass spectrometry (HPLC-ESI-MS/MS), (1)H nuclear magnetic resonance (NMR) and (13)C-NMR spectra. The two anthocyanins (cyanidin-3-glucoside with a purity of 92.25% and cyanidin-3-rutinoside with a purity of 93.07%) identified were consistent with those present in raspberries. These findings provided an effective and feasible method for extraction, isolation and purification of anthocyanins from natural plant resources.